Investigation of group interests structure - Lapė, J.; Abariūnaitė, A.; Gutauskienė, L. (Psichologija, 1983)
The structure of group interests of schoolchildren has been investigated using the adapted W Hennig technique. 21 groups of pupils of general and vocational technical education schools have been studied. The range, importance, interrelations, and structure of group interests as well as the difference in interests of separate groups have been revealed. It has turned out that further improvement of interest structure research technique by W. Hennig is expedient. The scope of pupil’s interests should be broadened, and more reliable means for the establishment of interrelation between interests should be sought.